2017
DOI: 10.1111/josh.12500
|View full text |Cite
|
Sign up to set email alerts
|

Association of School Characteristics and Implementation in the X:IT Study—A School‐Randomized Smoking Prevention Program

Abstract: Our findings highlight the importance of considering the school context in future health prevention initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
(54 reference statements)
0
11
1
Order By: Relevance
“…Most school-based tobacco control programs are ineffective, but data from Brazil remain scarce [3-5]. Recent trials on tobacco prevention in the school setting have focused on including school teachers in the intervention [6-8], with others involving families [9,10]. However, these studies concluded that the students’ environment (ie, peer group as well as parental behavior and school policies) plays a role in smoking initiation in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Most school-based tobacco control programs are ineffective, but data from Brazil remain scarce [3-5]. Recent trials on tobacco prevention in the school setting have focused on including school teachers in the intervention [6-8], with others involving families [9,10]. However, these studies concluded that the students’ environment (ie, peer group as well as parental behavior and school policies) plays a role in smoking initiation in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Most school-based curricula are ineffective, and data from Brazil remain scarce. 18–20 The most recent trials on tobacco prevention in the school setting have focused on including school personnel or sports trainers in the intervention 21–23 and others focused on involving the families, 24 25 but all of these studies concluded that the environment of the student (ie, the peer group but also parental behaviour, school policies, etc) plays a role in smoking initiation in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…As was the case for the evaluation of X:IT [19–21, 25], we will conduct a detailed process evaluation among teachers and students focusing especially on those from low SEP. The process evaluation is based on questions added to the student and school coordinator questionnaires concerning the implementation of the study, e.g.…”
Section: Methods and Designmentioning
confidence: 99%
“…The intervention was developed and implemented by the Danish Cancer Society. The Centre for Intervention Research was responsible for thorough scientific evaluation of implementation and effect of the intervention [1821]. The X:IT intervention was developed using the Intervention Mapping Protocol as a systematic planning tool [22] and the Theory of Triadic Influences as theoretical framework [23].…”
Section: Introductionmentioning
confidence: 99%